An Assessment of Socio-Economic Factors explaining Pupil Dropout in UPE Schools of Nyabihoko Sub- County, Ntungamo District - Abert, Musinguzi (Kabale University, 2022)
A Dissertation Submitted to the Directorate of Postgraduate training in Partial Fulfilment of the Requirements for the Award of a Master of Arts in Education Management of Kabale University